Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1093/ajcn/nqac216
|View full text |Cite
|
Sign up to set email alerts
|

Relative validity of a mobile AI-technology–assisted dietary assessment in adolescent females in Vietnam

Abstract: Background There is a gap in data on dietary intake of adolescents in low- and middle-income countries. Traditional methods for dietary assessment are resource intensive and lack accuracy with regards to portion size estimation. Technology assisted dietary assessment tools have been proposed but few have been validated for feasibility of use in LMICs. Objectives We assess the relative validity of FRANI (Food Recognition Assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…After searching for relevant articles in PubMed, 198 results were found and 7 clinical studies were considered relevant for inclusion [6][7][8][9][10][11][12]. Table 1 provides a brief overview of the studies included in this analysis (five randomized controlled trials, two crossover studies, and a pilot trial).…”
Section: Resultsmentioning
confidence: 99%
“…After searching for relevant articles in PubMed, 198 results were found and 7 clinical studies were considered relevant for inclusion [6][7][8][9][10][11][12]. Table 1 provides a brief overview of the studies included in this analysis (five randomized controlled trials, two crossover studies, and a pilot trial).…”
Section: Resultsmentioning
confidence: 99%
“…The second study used mobile phone photos taken by participants to classify foodstuffs and estimate nutrient intakes [17 ▪ ]. The same system was validated in Vietnam [18 ▪ ]. Another group focused on food labels, demonstrating that natural language processing models could accurately determine nutrient contents of food from images of their packaging [19].…”
Section: Population-level Studies Of Disease Riskmentioning
confidence: 99%
“…When evaluating dietary assessment apps, participant and researcher efficiencies vary based on the input method [32], with food photography and automated image scoring leading to the greatest gains in efficiency. Martin et al [50] demonstrated that food photography could result in a smaller error than self-report, and automated image scoring using AI was comparable with or more accurate than trained dieticians in calculating nutrients [51][52][53]. Keeney et al [34] showed increased efficiency for photo-based versus database entry caloric analysis (35 min/wk vs 85-90 min/wk).…”
Section: Principal Findingsmentioning
confidence: 99%